Population structure of Miscanthus sacchariflorus reveals two major polyploidization events, tetraploid-mediated unidirectional introgression from diploid M. sinensis, and diversity centred around the Yellow Sea. (20th September 2018) - Clark, Lindsay V; Jin, Xiaoli; Petersen, Karen Koefoed; Anzoua, Kossanou G; Bagmet, Larissa; Chebukin, Pavel; Deuter, Martin; Dzyubenko, Elena; Dzyubenko, Nicolay; Heo, Kweon; Johnson, Douglas A; Jørgensen, Uffe; et al.
Abstract: Background and Aims: Miscanthus, a C4 perennial grass native to East Asia, is a promising biomass crop. Miscanthus sacchariflorus has a broad geographic range, is used to produce paper in China and is one of the parents (along with Miscanthus sinensis ) of the important biomass species Miscanthus × giganteus . The largest study of M. sacchariflorus population genetics to date is reported here. Methods: Collections included 764 individuals across East Asia. Samples were genotyped with 34 605 single nucleotide polymorphisms (SNPs) derived from restriction site-associated DNA sequencing (RAD-seq) and ten plastid microsatellites, and were subjected to ploidy analysis by flow cytometry. Key Results: Six major genetic groups within M. sacchariflorus were identified using SNP data: three diploid groups, comprising Yangtze ( M. sacchariflorus ssp. lutarioriparius ), N China and Korea/NE China/Russia; and three tetraploid groups, comprising N China/Korea/Russia, S Japan and N Japan. Miscanthus sacchariflorus ssp. lutarioriparius was derived from the N China group, with a substantial bottleneck. Japanese and mainland tetraploids originated from independent polyploidization events. Hybrids between diploid M. sacchariflorus and M. sinensis were identified in Korea, but without introgression into either parent species. In contrast, tetraploid M. sacchariflorus in southern Japan and Korea exhibited substantial hybridization and introgression with local diploid M. sinensis . Conclusions: Genetic data indicated that the land now under the Yellow Sea was a centre of diversity for M. sacchariflorus during the last glacial maximum, followed by a series of migrations as the climate became warmer and wetter. Overall, M. sacchariflorus has greater genetic diversity than M. sinensis, suggesting that breeding and selection within M. sacchariflorus will be important for the development of improved M. × giganteus. Ornamental M. sacchariflorus genotypes in Europe and North America represent a very narrow portion of the species' genetic diversity, and thus do not well represent the species as a whole.